Rapid Degradation of Nitrochlorobenzene by Activated Persulfate Oxidation With Biochar Supported Nanoscaled Zero Valent Iron - Wang, Xiang; Deng, Rufeng; Shen, Wenbo; Huang, Jianbo; Li, Qun; Zhao, Yuanchao; Wan, Jinzhong; Zhou, Yan; Long, Tao; Zhang, Shengtian (Frontiers in Chemistry, 2021)
Although pesticide intermediates are a kind of typical toxic pollutants in contaminated sites, the remediation of which in groundwater and soils is of limited concern. In the present study we investigated the performance of a novel heterogeneous oxidation system, biochar supported nanoscaled-zero valent iron (nZVI/BC) activated persulfate (PS), in the oxidative degradation of nitrochlorobenzene (NCB), a typical pesticide intermediate. Peanut shell based nZVI/BC was prepared and used as the PS activator. The degradation kinetics of m-, p-, and o-NCB isomers in aqueous phase were investigated. The effects of BC/nZVI composition (Fe/BC mass ratio), the amount of BC/nZVI and PS, and initial contaminant concentration on NCB removal were also examined. Results suggest that over 90% removals of three NCB isomers could be obtained by the nZVI/BC activated PS system at initial NCB concentration of 10 mg• L-1. The combination of nZVI/BC composite and PS showed superior performance to PS alone. The optimal treatment condition was supposed as the Fe: BC ratio of 1:1, Fe amount of 6 mmol• L-1, and the mole ratio of Fe to perfulfate of 1:1.